Universal "Chip Based Smart Card" Snooping Device - Denamany, Dimitri (Universiti Teknologi Petronas, 2004)
The objective of this project is basically to design, build and test a Universal "Chip Based Smart Card" Snooping Device. This device would function to notify its user of the actual communication between the smart card and the smart card reader. The existence of this device not only serves as an educational tool but also saves a lot of time and money that are spent on debugging by smart card manufacturing companies. In addition to that, technological advances in the smart card world can also be sped up with the help of this device for research and testing. The hardware design of the project has been divided into 3 main sections, the snooping module, the communication module and the processing module. The snooping module taps the data, the communication module formats, encodes and transfers the data to the processing module, and lastly the processing module translates the data into useful information and display's it. The project has been divided into two major milestones where the first one was to set up the snooping device prototype with the processing module being a Computer. The second milestone on the other hand is the final design itself which would be to replace the Computer with a PALM in order to make it portable and affordable. This report gives a complete and detailed illustration on the hardware and software design process for the Universal "Chip Based Smart Card" Snooping Device. All aspects from the design decision, the underlying transmission protocols and also programming logics have been dissected and elaborately explained in the report. The design presented is a complete working device that fulfills all the objectives that have been set. The hardware device is certainly good enough to be marketed as it works flawlessly and achieves the most important objective of the project, which is to obtain the data transfer between the card and the smart card reader.